Penyuluhan Moderasi Beragama dalam Rangka Mewujudkan Harmonisasi di Lembaga Pendidikan - Munir; Farida Isroani (Edujavare Publishing, 2023)
In this era of globalization, educational institutions have a central role in shaping a person's character and mindset. Religious moderation plays a crucial role in forming a balanced understanding of religious teachings, encouraging attitudes of tolerance, and promoting dialogue between faiths. This article aims to dig deeper into the importance of counseling on religious moderation in efforts to achieve harmonization in educational institutions. The service research method adopts participatory methods to explore the impact of religious moderation counseling in realizing harmonization in educational institutions. Data will be collected through various methods, including participant observation, in-depth interviews with related parties, and document analysis techniques related to education and diversity programs at the institution using a descriptive qualitative approach technique. The results of this service research show that counseling on religious moderation in educational institutions can significantly increase attitudes of tolerance, a balanced understanding of religion, and the ability to dialogue between faiths, forming a strong foundation for realizing harmonization in the educational environment.